Automatic matching of software component requirements using semi-formal specifications and a CBSE ontology - Andreou, Andreas S.; Papatheocharous, Efi (My University, 2015)
One of the most significant tasks of component-based software development is concerned with finding suitable components for integration. This paper introduces a novel development framework that promotes reusability and focuses on assessing the suitability level of candidate components. A specifications profile is first created using a semi-formal natural language that describes the desired functional and non-functional properties of the component(s) sought. A parser automatically recognizes parts of the profile and translates them into instance values of a dedicated CBSE ontology, the latter addressing issues of components' reusability. Available components on the market are also stored as instances of the CBSE ontology. Matching between required and offered component properties takes place automatically at the level of the ontology items and a suitability ratio is calculated that suggests which components to consider for integration.
Keywords: Components; Ontology; Reuse; Semi-formal specifications matching